To find \(m\angle D\), we first need to consider the fact that the sum of the angles in any triangle is always 180 degrees.
In triangle \( \Delta DEF \):
\[ m\angle D + m\angle E + m\angle F = 180^\circ \]
Given \( m\angle E = 45^\circ \) and \( m\angle F = 25^\circ \):
\[ m\angle D + 45^\circ + 25^\circ = 180^\circ \]
Combining the known angles:
\[ m\angle D + 70^\circ = 180^\circ \]
Now, we subtract 70 degrees from both sides:
\[ m\angle D = 180^\circ - 70^\circ = 110^\circ \]
Since triangles \( \Delta DEF \) and \( \Delta XYZ \) are similar, their corresponding angles are equal. Therefore, \( m\angle X \) corresponds to \( m\angle D \):
\[ m\angle X = m\angle D = 110^\circ \]
Thus, the measure of angle \( \angle X \) is:
\[ m\angle X = 110^\circ \]
So the final response for the measure of angle \( \angle D \) is 110.